The Role of Physical Education in Developing Students’ Motivation and Lifelong Physical Activity: A Pedagogical Perspective - Alixanov, Valeh; Salmanov, Vidadi; Talibova, Lale; Hasanov, Nazim; Zeynalli, Cavansir; Aliyev, Seymur (Physical Education Theory and Methodology, 2026)
Objectives. This conceptual narrative review examines how motivation functions as a structural mechanism linking pedagogical approaches in physical education to lifelong physical activity. Materials and Methods. Through a selective and interpretive synthesis of theoretical and empirical literature grounded in Self-Determination Theory (SDT) and models-based practice, this review develops an integrative conceptual model. Results. The synthesis demonstrates that specific features of pedagogical models (e.g., autonomy support in TGfU, affiliation in Sport Education, and peer support in Cooperative Learning) satisfy the basic psychological needs for autonomy, competence, and relatedness. Simultaneous satisfaction of these needs facilitates the internalization of motivational regulation—from controlled to more autonomous forms (identified, integrated, and intrinsic regulation)—which, in turn, promotes sustained engagement in physical activity beyond the school context. Hybrid integrative models demonstrate greater potential because they create coherent learning environments that reinforce these processes, whereas traditional and single-model approaches often lead only to short-term compliance and limited behavioral transfer. Conclusions. Transitioning toward system-oriented hybrid frameworks, with motivation positioned as a central organizing mechanism, is essential for physical education to promote autonomous motivation and lifelong physical activity habits. The review identifies the conditions under which this mechanism operates effectively or fails, thereby providing a conceptual foundation for curriculum reform and future research.